KARAKALPAK LEARNERS’ PHONOLOGICAL ERRORS IN LEARNING ENGLISH LANGUAGE, THEIR REASONS CONSEQUENCE - Muratbaeva Umida Taumuratovna (Journals Park Publishing, 2022)
Phonology is one of the most challenging part of any language, one phoneme can considerably change the meaning of the sentence . Over the past ten years in the teaching of foreign languages, and primarily English, there has been a significant update of methodological training lessons and teaching materials. According to the well-known methodologist, graduates of Karakalpak schools know English Grammar much better than productive skills , but yet a poor pronunciation that sets them apart from the pronunciation of Europeans. But, despite this, most of them avoid contact with native speakers of foreign languages, even when they are the initiators of communication. Europeans communicate easily, without complexes about their pronunciation, using no more than 3-4 types of tense forms in speech and not special worrying about the presence of errors in your speech.